No Impact of the Analytical Method Used for Determining Cystatin C on Estimating Glomerular Filtration Rate in Children - Alberer, Martin; Hoefele, Julia; Benz, Marcus R.; Bökenkamp, Arend; Weber, Lutz T. (Frontiers in Pediatrics, 2017)
Background: Measurement of inulin clearance is considered to be the gold standard for determining kidney function in children, but this method is time consuming and expensive. The Glomerular filtration rate (GFR) is on the other hand easier to calculate by using various creatinine- and/or cystatin C-based formulas. However, for the determination of serum creatinine and cystatin C, different and non-interchangeable analytical methods exist. Given the fact that different analytical methods for the determination of creatinine and cystatin C were used in order to validate existing GFR formulas, clinicians should be aware of the type used in their local laboratory. In this study, we compared GFR results calculated on the basis of different GFR formulas and either used serum creatinine and cystatin C values as determined by the analytical method originally employed for validation or values obtained by an alternative analytical method to evaluate any possible effects on the performance. Methods: Cystatin C values determined by means of an immunoturbidimetric assay were used for calculating the GFR using equations in which this analytical method had originally been used for validation. Additionally, these same values were then used in other GFR formulas that had originally been validated using a nephelometric immunoassay for determining cystatin C. The effect of using either the compatible or the possibly incompatible analytical method for determining cystatin C in the calculation of GFR was assessed in comparison with the GFR measured by creatinine clearance. Results: Unexpectedly, using GFR equations that employed cystatin C values derived from a possibly incompatible analytical method did not result in a significant difference concerning the classification of patients as having normal or reduced GFR compared to the classification obtained on the basis of creatinine clearance. Sensitivity and specificity were adequate. On the other hand, formulas using cystatin C values derived from a compatible analytical method partly showed insufficient performance when compared to creatinine clearance. Conclusion: Although clinicians should be aware of applying a GFR formula that is compatible with the locally used analytical method for determining cystatin C and creatinine, other factors might be more crucial for the calculation of correct GFR values.